О разложении в ряд по начальным значениям и параметрам решений дифференциальных уравнений с разрывной правой частью - Ахметов, М.У. (Український математичний журнал, 1993)
The conditions under which .solutions of equations with discontinuous right-hand side depend analytical ly on the initial conditions and parameter are investigated. A definition is introduced to specify this depended e and the existence of a surface of discontinuity.